1990
DOI: 10.1002/hep.1840120619
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of liver P-450III cytochromes in choline-deficient rats: Implications for the erythromycin breath test as a parameter of liver function

Abstract: Progressive liver fibrosis in rats develops when they are fed a diet deficient in choline. This diet also results in a pronounced and selective decrease in the liver microsomal content of a phase I drug-metabolizing enzyme belonging to the cytochrome P-450III gene family. Because P-450III cytochromes characteristically catalyze the N-demethylation of erythromycin, we believed that the production of breath CO2 from erythromycin would be dramatically reduced in choline-deficient rats. However, when 12 choline-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1993
1993
2003
2003

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…It has been reported that the amount of CYP is reduced in CD-fed and aged rats, and the degree of reduction in each CYP is regulated in a different way. [8][9][10][11] Therefore, it seems that the content of each CYP isozyme in CD-fed and aged rats might be different from that in control rats, and the contribution of CYP isozymes, except for CYP1A2, to acetanilide and caffeine metabolism could not be neglected in these rat models.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that the amount of CYP is reduced in CD-fed and aged rats, and the degree of reduction in each CYP is regulated in a different way. [8][9][10][11] Therefore, it seems that the content of each CYP isozyme in CD-fed and aged rats might be different from that in control rats, and the contribution of CYP isozymes, except for CYP1A2, to acetanilide and caffeine metabolism could not be neglected in these rat models.…”
Section: Discussionmentioning
confidence: 99%
“…The specific activity of [8][9][10][11][12][13][14] C] caffeine was adjusted to 1924 Bq/nmol by dilution with unlabeled caffeine. Control, CDfed, aged, and MC-treated rat hepatic microsomes (0.125, 0.25, 0.0625, and 0.025 mg, respectively) were preincubated with 50 ml anti-rat CYP1A1 or CYP1A antibody for 30 min at room temperature prior to the measurement of caffeine metabolite formation.…”
Section: Quantitation Of Cyp1a2 In Hepatic Microsomesmentioning
confidence: 99%
See 1 more Smart Citation